In Defense of Imperfection - Wong, Desmond; Redden, Mikayla (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2025)
The demand for perfect solutions to complex institutional problems creates excessive, ever-changing barriers for racialized peoples working toward transformative justice. The same demand is not made of the methods used to adopt the emerging technologies which appeal to the libraries desire to appear in perpetual growth. This paper employed autoethnographic analysis and Storywork to understand and make meaning from our lived experiences as racialized librarians in relation to the sociopolitical spaces in which we work. These methodologies allowed us to expose complexities and vulnerabilities in our experiences with community-led work to return sacred Knowledge and offered us a means to critique the systems in which we operate and call upon our colleagues to embrace solutions that are gradual, decentralized, and imperfect. In this article, we make a series of calls to our colleagues as a means of engaging their thinking on unchecked assumptions that create greater barriers, more labour and burnout racialized colleagues. These calls create an ethic in place of best practices that challenge our profession to be responsive to local issues in relational ways. We offer this defense of imperfection as a means of bringing attention to the labour of social justice work within our profession and to ask all of our colleagues to embrace and make imperfect solutions possible.